2020
DOI: 10.1155/2020/5194508
|View full text |Cite
|
Sign up to set email alerts
|

Ellagic Acid-Derived Urolithins as Modulators of Oxidative Stress

Abstract: Oxidative stress is a state of excess of prooxidative species relative to the antioxidant defenses (enzymatic and nonenzymatic) in a living organism. The consequence of this imbalance is damage of the major cellular macromolecules (carbohydrates, lipids, proteins, and DNA), which further leads to a gradual loss of tissue and organ function. It has been shown that oxidative stress plays an important role in the pathogenesis of many chronic diseases (cardiovascular, metabolic, and neurodegenerative diseases and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
81
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(84 citation statements)
references
References 85 publications
2
81
0
1
Order By: Relevance
“…Other biomolecules found in WS that can be involved in the antioxidant and anti-inflammatory activities are the ellagitannins. In the gastrointestinal tract, ellagic acid, released from ellagitannins, is metabolized by the colonic microorganisms to urolithins, important modulators of oxidative stress and inflammatory action [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Other biomolecules found in WS that can be involved in the antioxidant and anti-inflammatory activities are the ellagitannins. In the gastrointestinal tract, ellagic acid, released from ellagitannins, is metabolized by the colonic microorganisms to urolithins, important modulators of oxidative stress and inflammatory action [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…As a result of this imbalance, important cellular macromolecules (lipids, carbohydrates, proteins and DNA) are damaged. Oxidative stress is also associated with the manifestation of many chronic diseases, such as metabolic, neurodegenerative, cardiovascular, lung, kidney and cancer diseases [ 53 , 54 ]. Several antioxidants have been described that have a beneficial effect against oxidative stress, including PUN, and metabolized EA and urolithins.…”
Section: Pharmacological Effect Of Punicalagin and Metabolitesmentioning
confidence: 99%
“…In addition, even upon high free EA intake, EA concentration in plasma was always quite low [ 11 ]. It has been demonstrated that in the grand intestine tract, EA undergoes an extensive metabolism by the gut microbiota providing urolithins, which are 25–80-fold more bioavailable and much better absorbed than EA [ 12 , 13 ]. Based on these data, interest has significantly increased in recent years for the development of delivery systems that might increase the solubility in water and bioavailability of EA, preserve its structural integrity, and warrant its controlled release at the physiological target [ 14 ].…”
Section: Introductionmentioning
confidence: 99%